Primitive neuroectodermal tumor with inferior vena cava thrombus: A rare case report (Indian Journal of Case Reports, 2020)
Primitive neuroectodermal tumors (PNETs) are rare type of small cell, aggressive tumors, commonly seen in the central nervous system, and PNET of the kidney with inferior vena cava thrombus is an extremely uncommon presentation of this entity. There are no established distinctive signs or radiological characteristics for diagnosis, but a majority of cases report positivity for CD99 marker. The patients usually present in the advanced stages of the disease and require progressive techniques of immunohistochemical analysis and expertise of multidisciplinary team of physicians to arrive at a correct diagnosis and have a proper management. Although rare, these tumors should be considered in the differential diagnosis of all patients with large renal masses, especially in the younger population. We present a case of a 23-years-old female, with PNET of the left kidney, treated with radical nephrectomy and adjuvant chemotherapy.